Pemberdayaan Remaja Putri dalam Pencegahan Anemia melalui Edukasi Kesehatan - Nurfadhila Nurfadhila; I Kadek Dwi Swarjana (Yayasan Inspirasi El Burhani, 2026)
Introduction: Anemia is a condition where the hemoglobin (Hb) level in the blood is lower than normal, reducing the blood's ability to transport oxygen to all body tissues. Objective: This community service activity aims to determine the knowledge of adolescent girls regarding anemia prevention at SMAN 1 Polewali Mandar. Method: This community service activity involved health education through counseling and leaflet distribution. This activity was held on December 10, 2025, at SMAN 1 Polewali Mandar, for 11th-grade female students and was attended by 50 adolescent girls. Result: The community service activity was conducted with adolescent girls using educational methods, leaflet distribution, discussions, and demonstrations of iron supplementation. This activity began with a pretest to measure the girls' initial knowledge, followed by health education and concluded with a posttest to evaluate knowledge improvement. Conclusion: This activity received feedback from the students, indicating that their knowledge improved after the material was presented.